Enteral beslenme: Bakımda güncel yaklaşımlar - (:unkn) unknown (My University, 2013)
Nazogastrik veya nazoenterik tüple enteral beslenen hastalarda en sık gastrointestinal, mekanik ve metabolik komplikasyonlar gelişmektedir. Bu komplikasyonlar basitten, yaşamı tehdit edici boyuta kadar ulaşabilir ve hastanın yetersiz beslenmesine, iyileşme sürecinin olumsuz etkilenmesine ve hastanede kalış süresinin uzamasına yol açar. Beslenmenin başarısı ve komplikasyonların en aza indirilmesi uygun bakım girişimleriyle sağlanabilir. Bu makalede enteral beslenmede güncel bakım yaklaşımları yer almaktadır.

The most common complications developed in patients with enteral nutrition by nasogastric or nasoenteric are gastrointestinal, mechanical and metabolic. These complications can be simple or can reach life-threatening levels. It may cause under-nutrition of patients, diverse effects on healing process and prolonged hospitalization. Success of nutrition and reduction in complication rate can be obtained by patient care approaches in accordance with evidence-based guidelines and recommendations. In this paper, current approaches to enteral nutrition are presented.
Enteral nutrition: Current approaches in the care
Keywords: Yoğun Bakım, Tıp